Norms for multivariate diagnosis of nutrient imbalance in the east African highland bananas (Musa spp. AAA) - Wairegi, L.W.I.; Asten, Piet J.A. van (Informa UK Limited, 2011)
Despite low yields and soil fertility problems, fertilizer use in the East African Highland banana (AAA-EA) production is absent. High fertilizer costs increase the need for site-specific fertilizer recommendations that address deficiencies. This study aimed to derive and compare norms for AAA-EA bananas, using Compositional Nutrient Diagnosis (CND), Diagnosis and Recommendation Integrated System (DRIS), and a DRIS that includes a filling value (DRIS-Rd), and study nutrient interactions. Data on foliar nitrogen, phosphorus, potassium, calcium, and magnesium concentrations, and plant performance were obtained from 300 plots in Uganda. CND indices were closely related to DRIS and DRIS-Rd indices (R2 > 0.965). Four nutrient interactions were common in both low and high bunch weight subpopulations. Although the three approaches can be used to determine nutrient imbalances in AAA-EA bananas, we recommend CND for ease of use. Diagnosis of nutrient deficiencies should be based on methods that identify plant nutritional imbalances.